Management of delayed corneal epithelial healing after refractive surgery: five case reports - Yan, Chunxiao; Jin, Lin; Zhang, Qiaosi; Liu, Xiaoyu; Yu, Taorui; Zhao, Fangkun; Mu, Yanan; Xu, Jun; Zhang, Lijun (Frontiers in Medicine, 2025)
BackgroundTransepithelial photorefractive keratectomy using Smart Pulse Technology (SPT-TransPRK) is currently the leading method for superficial refractive surgery, offering advantages such as a non-contact procedure, shorter operation times, and excellent patient cooperation. Laser ablation of the corneal epithelium, Bowman’s membrane, and the stroma can effectively correct refractive errors. Thus, the complete healing of the corneal epithelium post-surgery is essential for ensuring good vision. Refractive surgeons should enhance their understanding of corneal wound healing mechanisms and focus on the repair of the corneal epithelium following refractive surgery to ensure the quality of visual health of patients.Case presentationA total of five patients experienced varying degrees of delayed corneal epithelial healing following refractive surgery. In Case 1, unhealthy corneal epithelial debris was removed, and ophthalmic ointment was applied to cover the eyes instead of using bandage contact lenses (BCLs) to reconstruct the corneal epithelial barrier. This approach was also successfully implemented in Case 2. Furthermore, amniotic membrane transplantation (AMT) can quickly establish a corneal barrier and promote corneal epithelial regeneration, especially in cases of extensive corneal epithelial detachment. The remaining three patients were suspected of having corneal viral infections based on their medical history and the observation of corneal pathology using a slit lamp microscope. To prevent further infection and promote regeneration, topical steroid drops were discontinued early, and topical antiviral and corneal epithelial regeneration medications were administered alongside systemic antiviral therapy. Steroid drops were resumed after corneal epithelial healing to effectively prevent post-refractive haze.ConclusionDelays in corneal epithelial healing after refractive surgery should be taken seriously. BCLs, steroids, and both topical and systemic antiviral therapies should be properly utilized when there is a delay in corneal epithelial healing.